(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines the enhancement of independent learning activities among primary school pupils through methodological approaches applied in the subject of Technology. It analyzes pedagogical strategies that strengthen learners’ autonomy and proposes an improved methodological model based on the didactic potential of the Technology curriculum. The study highlights the development dynamics of self-regulation, planning, and reflective skills through active learning, project-based tasks, and hands-on activities. The results demonstrate that the proposed approaches significantly increase pupils’ engagement and effectiveness in independent learning.